EFFECT OF COASTAL ENVIRONMENT IN CLAY FACING BRICKS AND ROOF TILES - B. Sena da Fonseca; J.A.R. Simao; C. Galhano (European Scientific Journal, ESJ, 2013)
Materials made from clay, such as bricks or roof tiles are widely used in recent buildings. Their severe exposure to salt spray, common in coastal environments could cause premature degradation which leads into functional, aesthetic, economical and safety problems. The aim of this study is to analyze and quantify the physical and mechanical alteration caused by salt spray in modern facing bricks and roof tiles. For this purpose, one type of roof tile and two types of bricks were submitted to various stages of accelerated aging test by salt spray. Visually and binocular microscope inspection reveal visible degradation. The tests to evaluate the physical and mechanical characteristics of the bricks and tiles were made before, during and after the aging test, the results expose a general unfavorable trend in expected performance of the three types of materials. It was possible to identify the main intrinsic characteristics of the materials that have led to their degradation.